Fatores estruturadores da metacomunidade do Zooplâncton no Reservatório de Manso-MT - Paes, Nayara Dores da Silva (2017)
Much of the study in community ecology evaluates how changes in species composition from a local perspective. Recently, models have been developed that cover environmental and environmental processes, emphasizing a value of spatial products in the composition of species at broader scales. Therefore, the central objective of this study is to determine the importance of environmental and physical and environmental effects (particularly the effects of dispersion) on a composition of zooplankton species, particularly rotifers, cladocerans and copepods in a hydroelectric reservoir (MansoMT). For this, the points of 40 points distributed inside the reservoir At each point, I collected zooplankton samples by filtering 600 liters of water with a plankton netting with 68μm mesh. Measured the physical-chemical parameters of the water and mark as geographical coordinates of each sampled point. For an analysis of the environmental and environmental effects of a zooplankton composition, use a Partial Redundancy Analysis (pRDA). A variation in the composition of species found along the Manso reservoir resulted from both environmental processes and environmental processes. The importance of environmental factors and variables among the three zooplankton groups (Rotifera, Cladocera and Copepoda). However a spatial fraction as well as a full explanation of the models, increased the size of the organism. These results are in agreement with studies that found relationship between body size and dispersion for aquatic organisms. These responses suggest that the structure of the zooplankton metacommunity of the Manso-MT reservoir is caused not by one but by the combination of environmental and environmental processes.